Adsorption of Myoglobin onto Hydroxyapatite Modified with Metal Ions - Cristiane S. Farinas; Patrícia C. Reis; Helen C. Ferraz; Vera M.M. Salim; Tito L.M. Alves (Adsorption Science & Technology)
Optimization of the purification process remains a challenge in the production of proteins for pharmaceutical or industrial applications. In this context, the purpose of this work was to study the adsorption of myoglobin onto hydroxyapatite (HAp) modified with metal ions (Cu 2+ , Ni 2+ , Zn 2+ ), with the aim of its purification from a complex medium. The influence of pH and ionic strength on the adsorption process was evaluated using experimental design methodology. Experiments for determining the kinetics and adsorption isotherms were undertaken, allowing the determination of important equilibrium parameters required for scale-up. High adsorption capacities (ca. 90 mg myoglobin/g modified HAp) and rapid adsorption kinetics were observed. These results indicate the applicability of HAp as a support for pseudo-affinity chromatography.